Efficient Hydrogen Production on a 3D Flexible Heterojunction Material. Issue 21 (10th April 2018) - Yu, Huidi; Xue, Yurui; Hui, Lan; Zhang, Chao; Li, Yongjun; Zuo, Zicheng; Zhao, Yingjie; Li, Zhibo; Li, Yuliang
Abstract: A novel heterojunction material, with electron‐rich graphdiyne as the host and molybdenum disulfide as the catalytic center (eGDY/MDS), to produce ultraefficient hydrogen‐evolution reaction (HER) at all pH values is described. It is a surprise that the metallic conductor combined from two semiconductor materials, eGDY and MDS, leads to optimal free energy (Δ G H ) and enhancement in the intrinsic HER catalytic performances. The calculated and experimental results indicate that eGDY/MDS shows greatly enhanced catalytic activities and high stabilities in both acidic and alkaline conditions; these approach the outstanding performances of the state‐of‐the‐art noble‐metal‐based catalysts. The eGDY/MDS shows better activity than Pt/C in alkaline media and remarkable enhancement in photocurrent density. The high catalytic activity of eGDY/MDS originates from facilitated electronic transfer kinetics, high conductivity, more exposed catalytic active sites, and excellent mass transport. Abstract : A novel flexible heterojunction material with electron‐rich graphdiyne as the host material for ultraefficient hydrogen‐evolution reaction is prepared using a facile, scalable strategy. The catalyst shows high activity and stability, and approaches state‐of‐the‐art noble‐metal‐based catalysts in acidic and alkaline conditions. This is likely to lead to breakthroughs of the traditional concepts for building new catalysts and to a new understanding of electrocatalysis.